PENERAPAN METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE SMART DALAM PENGAMBILAN KEPUTUSAN TERKAIT EVALUASI SISWA TERBAIK (STUDI KASUS: SMK DARUR ROJA) - Azmiyansyah Rizky; Iis Aisyah (Journal of Research and Publication Innovation, 2025)
Decision Support Systems (DSS) are essential to evaluate students in a more objective, effective, and planned manner. At SMK Darur Roja, assessments are still carried out conventionally and have not fully utilized existing data optimally. So far, assessments to find the best students have only focused on academic grades, while other important aspects such as attendance, behavior, and participation in extracurricular activities have not been the main focus. This commonly used method is prone to human error, takes a long time, and can produce subjective decisions. This study aims to design and implement a web-based DSS using the Simple Multi Attribute Rating Technique (SMART) method. The SMART method was chosen because it has the advantage of easy calculations, flexible weight adjustments, and can show alternative rankings based on the final results of predetermined criteria. This system was created using the PHP programming language and MySQL database. The results of the implementation show that the system can work as expected and provide accurate results, with a user satisfaction rate of 83.36%. It is hoped that this system can help schools in determining the best students comprehensively and fairly.